The Analysis of Speech Acts Found in The Talk Show "Hitam Putih' on Trans 7 TV (Episode 18th December 2017) - Karmila, Karmila; Rohmana, Rohmana; Aderlaepe, Aderlaepe (Journal of Teaching English, 2019)
This thesis is about the analysis of speech acts found in the talk show â€œHitam Putihâ€ on Trans 7 (Episode 18th December 2017). The research question of this thesis were (1) What kinds of the illocutionary acts used in host and main guest stars utterance in â€œHitam Putihâ€ talk show? And (2) How perlocutionary acts implied in host and main guest stars utterance in â€œHitam Putihâ€ talk show?. The objectives of this research were to identifying and analyze the types of the illocutionary acts and the perlocutionary acts implied in host and main guest stars utterance in â€œHitam Putihâ€ talk show.This research used a qualitative method to describe and analyze the utterances. The technique of data collection were (1) Download the video of talk show Hitam Putih from YouTube. (2) Transcribe the conversation by listen to the video in several times. (3) Reads and observes dialog from the script. (4) Classified the types of illocutionary acts which finding in conversation. The technique of data analysis were (1) The researcher identified the illocutionary act and perlocutionary act from the host and main guest stars utterance in Hitam Putih talk show. (2) Described and analized the utterances which include illocutionary and perlocutionary acts by using pragmatic approach. (3) Concluding the data analysis.The result of this thesis show that assertive illocutionary acts is the dominant types of speech act. There are 29 assertive of illocutionary acts, 14 directive of illocutionary acts, 15 expressive of illocutionary acts, 1 commissive of illocutionary acts. Perlocutionary acts which occurs between the speakers and the listener in the form of give statements, give questions, body language, expressions and following the speakerâ€™s directions.